(untitled) (Research, Society and Development, 2022)
The research presents a study on quality management in military organizations. The main objective of the research is to know the quality management practices developed in the barracks of the Curado Military Complex, in Recife-PE of the Brazilian Army. The relevance of the study in the military complex points out relevant characteristics of each barracks, being able to infer discussions of the sustainable context in each field of action. The methodology used was defined through a qualitative-quantitative analysis, where a questionnaire was proposed for data collection and analysis in eleven barracks, it contains ten questions, eight objective and two open. The questions were directed to the managers of the military units that work in the management of each unit, and refer to management practices, use of quality tools and managers’ perception in relation to the development of actions aimed at the continuous improvement of processes. The results show that 66% of the researched barracks use some quality tool, indicating signs of control in the environment, and relating important advances in process control. Finally, quality tools help in the constructive process, when implemented, in achieving improvements in organizations.